Optimizing the Roles of Posbakum and Islamic Organizations in Medan City for Child Victims of School Violence - Lubis, Syofiaty; Yuslem, Nawir; Panjaitan, Budi Sastra; Afendi, Hazrul (IAIN Manado, 2024)
This research relates to optimizing the role of Medan City Islamic Organization legal aid posts in providing legal assistance to child victims of school violence. It is a socio-empirical legal study in the category of sociological-empirical research using a qualitative approach. The research focuses on social and legal phenomena in society, specifically the role of Islamic mass organization legal aid posts in Medan City in providing legal assistance to child victims of school violence. Data were collected through interviews with the Medan City Islamic Organization Posbakum and analysis of Law Number 23 of 2002 concerning Child Protection, as well as from legal materials providing explanations of primary legal materials obtained through literature studies related to the research problem. The research results show that the implementation of the Aisyiyah Legal Aid Post (Posbakum) in the North Sumatra region can help provide legal assistance for child victims of school violence by offering consultation, legal aid, and advocacy. However, to provide more optimal legal assistance, efforts are still needed to improve the quality and quantity of resources owned by Posbakum Aisyiyah. Furthermore, the active role of all parties, especially the government and society, is crucial to support the optimization of Posbakum Aisyiyah's implementation and enhance legal protection for child victims of school violence.